Penerapan model quantum teaching untuk meningkatkan hasil belajar IPA siswa kelas III.B SD Negeri 188 Pekanbaru - Mahmud Alpusari; Lazim N; Sihol Martua (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2019)
This research is motivated by the low value of Natural sciense in grade IIIB students at SDN 188 Pekanbaru, this is caused by several factors, namely 1) The lack of teachers involves students in active learning, 2) Teachers rarely do varying learning methods so they use the lecture method more 3) More theory than the practice given by the teacher, 4) The teacher does not understand the personal characteristics of each student. For this reason, researchers try to apply an interactive learning model and create a fun and enjoyable learning environment for students, namely the Quantum teaching model. Which aims to improve the learning outcomes of class IIIB students at SDN 188 Pekanbaru. This research is a classroom action research, carried out in 3 cycles with 2 meetings and 1 daily replication in each cycle, it aims to see the development of learning outcomes each cycle. Based on data from classroom action research, by applying the Quantum teaching model conducted from April 16 to May 10, 2018, it can be seen that there is an increase in the average student learning outcomes in each cycle, starting from the initial data collection of the average score of the basic score 67.5 in the implementation of cycle 1 the average student learning outcomes increased to 72.59, then in cycle 2 it increased to 76.28, then in cycle 3 it increased again to 80.36.This it can be concluded that the application of the Quantum teaching model can improve the Natural sciense learning outcomes of grade IIIB students at SDN 188 pekanbaru